Direct synthesis of ordered imidazolyl-functionalized mesoporous polymers for efficient chemical fixation of CO2. Issue 4 (21st November 2014) - Zhang, Wei; Liu, Tingying; Wu, Haihong; Wu, Peng; He, Mingyuan
Abstract : Synthesis of imidazolyl-functionalized ordered mesoporous polymers (IM-MPs) and their application as efficient heterogeneous catalysts for the cycloaddition of CO2 to epoxides. Abstract : Ordered imidazolyl-functionalized mesoporous polymers (IM-MPs) are directly synthesized by an evaporation-induced self-assembly method, which are further functionalized with bromoethane and employed as highly efficient and recyclable catalysts for the cycloaddition of CO2 to epoxides.